2022
DOI: 10.1093/jpepsy/jsac048
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and Patterns of COVID-19 Vaccination Intentions among Parents of Children with Type 1 Diabetes

Abstract: Objective To examine psychosocial, sociodemographic, medical, and coronavirus disease 2019 (COVID-19) experiences as correlates of COVID-19 vaccination intentions among parents of children with type 1 diabetes (T1D). Methods 121 parents of children with T1D ( M child age = 7.78 ± 1.70; M A1c = 8.3% ± 1.5%) in the mid-Atlantic and Southwest regions completed self-report measures in February to March 2021. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Previous studies conducted in the general adult population also showed that the awareness of vaccine safety is positively related to vaccination willingness (6-7). In addition, Kreps et al found that a decrease in the incidence of major adverse effects is associated with a higher probability of choosing a vaccine (8). A study also showed that vaccine safety is the top concern for COVID-19 vaccination intentions among children with diabetes (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies conducted in the general adult population also showed that the awareness of vaccine safety is positively related to vaccination willingness (6-7). In addition, Kreps et al found that a decrease in the incidence of major adverse effects is associated with a higher probability of choosing a vaccine (8). A study also showed that vaccine safety is the top concern for COVID-19 vaccination intentions among children with diabetes (9).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the perceived efficacy of the booster dose vaccine was positively related to vaccination behavior. Kreps et al found that the more significant the efficacy of the vaccine, the longer the protection time and the greater the vaccination probability (8). Diabetic patients are susceptible to SARS-CoV-2, which may be more inclined to consider the effectiveness of the COVID-19 vaccine before vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Glycemic imbalance was observed in only 2.5% of patients [ 61 ]. A US study among parents of children with T1D [ 62 ] with a mean age of 7.8 ± 1.7 years and mean HbA1c levels of 8.3 ± 1.5% in the Mid Atlantic and Southwest Regions, reported that higher HbA1c levels were associated with lower intention to vaccinate, with vaccine safety being the main parental concern. Moreover, higher parental vaccination intention was associated with child private insurance (compared to public), and shorter T1D duration [ 62 ].…”
Section: Concerns About Children and Adolescents’ Covid-19 Vaccinationmentioning
confidence: 99%